Value of sarcopenia in the resection of colorectal liver metastases—a systematic review and meta-analysis - Wagner, D.; Wienerroither, V.; Scherrer, M.; Thalhammer, M.; Faschinger, F.; Lederer, A.; Hau, H. M.; Sucher, R.; Kornprat, P. (Frontiers in Oncology, 2023)
Introduction: Sarcopenia is defined as decline in muscle function as well as muscle mass.Sarcopenia itself and Sarcopenic Obesity, defined as sarcopenia in obese patients, have been used as surrogates for worse prognosis in colorectal cancer. This review aims to determine if there is evidence for sarcopenia as prognostic parameter in colorectal liver metastases (CRLM).Methods: Pubmed, Embase, Cochrane Central, Web of Science, SCOPUS, and CINAHL databases were searched for articles which were selected in accordance with PRISMA guidelines. Primary outcomes were overall survival (OS) and disease-free survival (DFS). A random effects meta-analysis was conducted.Results: 949 studies were screened, after eliminating duplicates and screening of abstracts (n=111), 33 publications met inclusion criteria. Of them 15 were selected after close paper review and 10 were incorporated into the meta analysis comprising 825 patients. No significant influence of sarcopenia for OS (OR 2.802, p=0.4) or DFS (OR 1.203, p=0.5) was found although a trend was defined towards sarcopenia. Sarcopenia significantly influenced postoperative complication rates (OR 7.905, p=0.001) in two studies where data was available.Conclusion: Existing evidence on the influence of sarcopenia on postoperative OS as well as DFS in patients undergoing resection for CRLM exists. We were not able to confirm that sarcopenic patients have a significantly worse OS and DFS in our analysis although a trend towards this hypothesis was visible. Sarcopenia seems to influence complication rates but prospective studies are needed.